PERANAN PEMBELAJARAN BERBASIS MASALAH TERKAIT TEMA MAKANAN TERHADAP SIKAP SAINS SISWA - Sujana, Atep (Mimbar Sekolah Dasar, 2017)
The aim of this study is to determine the effect of problem-based learning on student’s science attitudes related to food theme’s. The method used is quasi experiment with pretest-posttest design. Subjects in the study were the students of grade V elementary school in Sumedang, amounting to 44 people and 15 classroom teachers. The instruments used consist of attitude scales, questionnaires, and interviews provided before and after problem-based learning. The results showed that there was an increase in student’s science attitude after learning, which can be seen from the increase of the average score of student’s science attitude from 82.00 to 83.4.Keywords: student’s science attitude, food, problem-based learning.